(untitled) (Journal of Asian Development Studies, 2025)
This study examines how learning organizations enable their employees to be more resilient at work. When times get tough, many companies struggle to maintain their employees’ motivation and stability, and few researchers have examined exactly what within the company helps this occur. Data were gathered from 313 respondents from pharmaceutical companies in Pakistan and tested our research idea using structural equation modelling using SmartPLS. We also discovered that if organizations follow practices of a learning organization, such as continuous learning opportunities, inquiry and dialogue, collaboration and team learning, empowerment towards a collective vision, a system to capture and share learning, connecting the organization to its environment, and strategic leadership, it makes employees feel more empowered in their jobs, and this empowerment then translates to improved resilience. We also discovered that this empowerment is a partial reason for workers’ resilience in learning organizations. The study employs two theories: Conservation of Resource Theory and the Broaden-and-Build Theory to explain why this happens. The findings provide managers with the message that they need to invest in developing an ideal learning organization, not just focus on stress-management training for individuals.